1878 The Relationship between GCS and Length of PICU Stay. (October 2012) - Nicholas, J; White, D
Abstract : Background: Our PICU, admitting 700 patients a year is the major trauma centre for East Anglia, UK. The Glasgow Coma Score (GCS range 3–15) offers practitioners a guide to the critical patient's conscious level. We wanted to consider the relationship between the patients's GCS at the trauma scene with the length of time the children were admitted within the PICU. Methods: Exploratory data was collected reviewing 42 paediatric head-trauma patient's notes for two years, January 2010 - November 2011, to ascertain if any correlation could be established between the GCS scores at the scene and the length of the child's PICU stay (range 1–17 days).Children aged 0–16 where included (youngest 2 months, oldest 15 years), children who had suffered non-accidental injuries were excluded, as where those who had died. Results: The results showed a correlation of: lower the GCS the higher the length of PICU stay, however statistically (R2 = 0.375), this could not be used to define all head injury admission length of stays, and other factors such as age may contribute. Conclusions: Emergency admissions effect the PICU's capability maintaining elective surgery, the ability to more accurate determine a patient length of stay is important in supporting work force planning, and supply purchasing. A lower GCS at the trauma scene did show some increased length of PICU admissions. The early GCS score could potentially offer a manager of a PICU an indication of the patient's estimated length of stay, a larger group and further research concerning other factors should be considered.